ANALISIS EFEKTIVITAS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA ALAMI KABUPATEN TANAH DATAR - Rimbun Budiman; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Effective use or management of working capital is an important factor to increase company profitability. This study aims to determine and analyze the effectiveness of working capital management in increasing the profitability of the Regional Water Comapny (PDAM) Tirta Alami, Tanah Datar Regency, West Sumatera Province. This research uses quantitative descriptive data. The data collection technique used is documentation and interview techniques on the financial data of the Tirta Alami Regional Drinking Water Company (PDAM) in Tanah Datar Regency, West Sumatra Province.. The Results of this study are as follows: The management of working capital on profitability at the Regional Water Company (PDAM) Tirta Alami, Tanah Datar Regency, West Sumatra Province has not been effective which causes a decrease in the rate of return on investment, but sometimes there is an increase. The decline in the ROE ratio caused by the company’s net profit experienced a significant increase compared to the provious year. Keywords: working capital, profitability (ROE).